Telomere maintenance in soft tissue sarcomas. Issue 5 (9th February 2017) - Eastley, Nicholas; Ottolini, Barbara; Garrido, Carmen; Shaw, Jacqueline A; McCulloch, Thomas Alasdair; Ashford, Robert U; Royle, Nicola J
Abstract : Soft tissue sarcomas (STS) are a diverse group of heterogeneous malignant tumours derived from mesenchymal tissues. Over 50 different STS subtypes are recognised by WHO, which show a wide range of different biological behaviours and prognoses. At present, clinicians managing this complex group of tumours face several challenges. This is reflected by the relatively poor outcome of patients with STSs compared with many other solid malignant tumours. These include difficulties securing accurate diagnoses, a lack of effective systemic treatments and absence of any sensitive circulating biomarkers to monitor patients throughout their treatment and follow-up. In order to progress STS's cells must evade the usual cellular proliferative checkpoints, and then activate a telomere maintenance mechanism in order to achieve replicative immortality. The purpose of this review is to provide an overview of STS genetics focusing particularly on these mechanisms. We will also highlight some of the key barriers to improving outcome for patients with STS, and hypothesise how a better understanding of these genetic characteristics may impact on future STS management.